TECHNOLOGY OF DEVELOPMENT OF CRITICAL THINKING AS A MEANS OF FORMING THE SKILLS OF FOREIGN LANGUAGE WRITTEN SPEECH OF HIGH SCHOOL STUDENTS IN PREPARATION FOR THE UNIFIED STATE EXAM - E. Al-Momani; N. Pelevina; A. Serdyukova (Вестник Северо-Кавказского федерального университета)
The article deals with the purpose, functions and requirements for the technology of critical thinking development in the process of teaching foreign-language written speech to high school students, considers different approaches to the definitions of the concepts «technology of critical thinking development}}, «written speech». The developed methodology of teaching foreign language written speech using the technology of developing critical thinking is presented, which is designed to form the skills of foreign language written speech of high school students in preparation for the Unified State Exam and to increase the effectiveness of the learning process.